Ultra-small single mesoporous carbon nanoparticles and preparation method and application thereof
Through the combined template method of block copolymer micelles and dopamine hydrochloride, ultra-small single mesoporous carbon nanoparticles were successfully prepared, solving the problems of large material size and irregular morphology in the prior art, and achieving a significant improvement in the electrochemical performance of the material.
Patent Information
- Application Number
- CN202510027443.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-08
AI Technical Summary
It is difficult to synthesize ultra-small, asymmetric, single mesoporous, hollow nanostructured materials in the prior art, and the traditional soft template micelles are unstable, resulting in large material sizes and irregular morphology.
Block copolymer micelles were used as soft templates, and SiO2 nanoparticles with particle sizes of 35-65nm were prepared through thermodynamic control and magnetic stirring reactions. Dopamine hydrochloride and SiO2@ single micelle were reacted to form a polydopamine-encapsulated SiO2@ single micelle composite. Finally, ultra-small single mesoporous carbon nanoparticles were removed by high-temperature carbonization and template removal.
The preparation of ultra-small single mesoporous carbon nanoparticles has been achieved, with large specific surface area, ultra-small particle size, large pore size and unique pore structure, which significantly improves the electrochemical performance of the material.
Smart Images

Figure CN119409179B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mesoporous materials, and more specifically, to ultra-small single mesoporous carbon nanoparticles and a preparation method and application thereof. Background Art
[0002] Hollow materials are biomimetic structural materials with large internal voids. Because of their diversity in nanoscale morphology, cavity structure and chemical composition, they can produce customized synergies between functional frameworks and encapsulated guest substances, and have been widely used in research fields such as catalysis, energy, and biomedicine in the past few decades. In the past decade, people have been committed to achieving precise morphological control and optimizing mesoscopic structures to manufacture hollow nanoparticles with asymmetric geometric structures, such as asymmetric hollow nanobottles, nanobowls, nanobadmintons, etc. The pioneering application prospects of these research results in various fields are unlimited, because they not only provide complex nanostructures (open shell structures), but also provide optimized physical and chemical properties, such as larger specific surface area, higher packing density, and improved mass / ion transport capabilities.
[0003] In particular, asymmetric hollow mesoporous materials are composed of the main part of the mesoporous cavity and radially open through holes. This structure can not only enhance the structural stability of the mesoporous core, but also increase the accessibility to a large number of active sites in the particle cavity while increasing the volume packing density. However, most of the existing asymmetric hollow nanoparticles have closed shell structures, uneven morphology, and uncontrollable synthesis processes.
[0004] The directed cooperative self-assembly method of amphiphilic molecules, such as hexadecyltrimethylammonium bromide (CTAB), Pluronic F127 triblock copolymer, is a general method for synthesizing mesoporous nanoparticles based on solution interface assembly. The rational introduction of appropriate amphiphilic soft templates and hard templates in the reaction system can create hollow nanostructures with asymmetric mesoporous channels. In the past three decades, these soft micelle directed assembly methods have been widely used to synthesize various asymmetric functional mesoporous materials. For example, badminton-shaped mesoporous hollow materials are used to explore the relationship between the structure of nanoparticles and biofluid dynamics, organ clearance and blood circulation. Another example is bowl-shaped mesoporous hollow materials, which are used in sodium ion and zinc ion capacitors. However, the existing asymmetric mesoporous hollow nanoparticles are large in size, generally hundreds of nanometers, or even above the micron level, which limits the mass transfer efficiency. For example, the patent No. 202410010874.9 discloses a raspberry-shaped mesoporous carbon sphere with a high specific surface area and a preparation method thereof, wherein the particle size of the mesoporous superstructure carbon sphere is 300-400nm. The large size and irregular morphology of these mesoporous materials are due to the difficulty of synthesizing ultra-small templates and the instability of traditional soft template micelles, which cause serious adhesion or easy phase transition to form impurity phases. So far, ultra-small, asymmetric mesoporous hollow materials have not been reported. Therefore, it is a major challenge to synthesize an ultra-small, asymmetric, single-mesoporous, hollow nanostructured material. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an ultrasmall single mesoporous carbon nanoparticle and a preparation method and application thereof, wherein the single mesoporous carbon nanoparticle has a large specific surface area, an ultrasmall particle size, a large pore size and a unique pore structure, which increases the active sites of chemical reactions, can provide better material transport channels, and has fast mass transfer kinetics, so that the electrolyte can diffuse rapidly in the particles through radial pores, thereby significantly improving the electrochemical properties of the material.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing ultrasmall single mesoporous carbon nanoparticles, comprising the following steps:
[0007] (1) using block copolymer micelles as soft templates, dissolving them in an ethanol solution to obtain a block copolymer solution with a concentration of 0.2-30 mg / mL, and then preparing a single micelle solution by a thermodynamic control method;
[0008] (2) deionized water, anhydrous ethanol and concentrated ammonia solution are mixed in a mass ratio of 10-20:1-24:5-10 to obtain solution A, tetraethoxysilane and anhydrous ethanol are mixed in a mass ratio of 10-50:1-5 to obtain solution B, the solution B is poured into the solution A, and stirred at room temperature for reaction for 2-10 hours; then dimethyldimethoxysilane is added, and stirred for reaction for 2-10 hours. After the reaction, SiO2 nanoparticles with a particle size of 100-300 nm are obtained by purification and drying;
[0009] (3) The SiO2 nanoparticles in step (2) are uniformly dispersed in an anhydrous ethanol solution to form an SiO2 anhydrous ethanol solution with a concentration of 1-10 mg / mL, and then the single micelle solution in step (1) is added dropwise to the SiO2 anhydrous ethanol solution under stirring, and then ammonia water is added to adjust the pH value to 7-9, and then SiO2@single micelle superstructure nanoparticles are obtained after purification and drying;
[0010] (4) The superstructured nanoparticles in step (3) are uniformly dispersed in an anhydrous ethanol solution to form a superstructured nanoparticle alcohol solution with a concentration of 1-5 mg / mL, and then deionized water and bis(2-hydroxyethyl)aminotri(hydroxymethyl)methane buffer are added to the superstructured nanoparticle alcohol solution, and ultrasonic treatment is performed for 5-15 minutes to make it uniformly dispersed, and then dopamine hydrochloride is added, and the reaction is stirred at room temperature for 2-10 hours to obtain a polydopamine-encapsulated SiO2@single micelle complex;
[0011] (5) The composite material in step (4) is centrifuged, washed and dried in sequence to obtain a pure sample, and then calcined in a nitrogen atmosphere at a heating rate of 1-5°C / min from room temperature to 350-800°C and maintained for 3-10 hours to obtain a SiO2@mesoporous carbon structure; finally, the composite material is treated with a sodium hydroxide solution at a temperature of 5-60°C for 4-10 hours to remove the silica template and generate ultrasmall single mesoporous carbon nanoparticles.
[0012] Furthermore, the block copolymer in step (1) is one of polystyrene-polyvinyl pyrrolidone-polyethylene glycol, polystyrene-polyacrylic acid-polyethylene glycol, polymethyl methacrylate-polyvinyl pyrrolidone-polyethylene glycol, polystyrene-polyvinyl pyrrolidone, and polystyrene-polyacrylic acid.
[0013] Furthermore, in step (1), the thermodynamically controlled temperature is 70-110° C. and the time is controlled to be 3-5 hours.
[0014] Furthermore, in the step (2), the mass ratio of the B solution, the A solution and the dimethyldimethoxysilane is 16-54:11-55:0.4-2.0.
[0015] Furthermore, the reaction in step (3) is a magnetic stirring reaction with a stirring speed of 300-600 r / min and a time of 0.5-5 h.
[0016] Furthermore, in the step (3), the volume ratio between the SiO2 anhydrous ethanol solution and the single micelle solution is 1:0.5-5.
[0017] Furthermore, in the step (4), the mass ratio of the superstructured nanoparticle alcohol solution, the deionized water, the buffer and the dopamine hydrochloride is 1:1-5:0.002-1:0.002-1.
[0018] Furthermore, in the step (5), the centrifugal speed is 8000-40000 r / min, the washing conditions are washing with deionized water and 95% ethanol solution for 2-6 times respectively; the drying temperature is 50-80°C, and the drying time is 10-20h; the concentration of the sodium hydroxide solution is 2M, and the mass ratio of the SiO2@mesoporous carbon structure to the sodium hydroxide solution is 1:50-120.
[0019] Another aspect of the present invention provides the following technical solution: ultra-small single mesoporous carbon nanoparticles, wherein the ultra-small single mesoporous carbon nanoparticles are hollow structures, open pores are arranged on the shell surface of the ultra-small single mesoporous carbon nanoparticles, and the particle size of the ultra-small single mesoporous carbon nanoparticles is 35-65nm; the specific surface area is 993-1312m 2 / g.
[0020] On the other hand, the present invention provides the following technical solution: application of ultra-small single mesoporous carbon nanoparticles in batteries, wherein the ultra-small single mesoporous carbon nanoparticles are used as positive electrodes, zinc sheets are used as negative electrodes, and aqueous zinc salt electrolytes are used to assemble aqueous zinc ion batteries.
[0021] The advantages of the present invention are:
[0022] 1. The present invention discloses an ultra-small single mesoporous carbon nanoparticle and a preparation method thereof. The surface of a silica ball is modified by dimethyldimethoxysilane, so that the group on the surface of the silica ball changes from -OH to -CH3. This process makes the silica ball appear hydrophobic. As a substrate, through the confinement of the silica ball, the subsequent ultra-small carbon nanoparticles form a single mesopore. Subsequently, dopamine hydrochloride is used as a carbon source to react with the SiO2@ single micelles dispersed in water. Dopamine will only be hydrolyzed and coated on the hydrophilic single micelles, and will not grow on the hydrophobic surface of the silica ball, thereby achieving the selective assembly of dopamine, that is, the single micelles and the carbon source self-assemble under the action of hydrogen bonds and van der Waals forces to form core-shell spherical particles. Finally, the single micelles are removed by high-temperature carbonization, and spherical mesoporous carbon is obtained by a double template method. The single mesoporous carbon nanoparticle has a large specific surface area (1312m 2 / g), with an ultra-small particle size of only 35-65nm, large pore size and unique pore structure (15-30 nm), which increases the active sites of chemical reactions, provides better material transfer channels, and has fast mass transfer power, allowing the electrolyte to diffuse rapidly within the particles through radial pores, significantly improving the electrochemical performance of the material.
[0023] 2. The present invention discloses an application of ultra-small single mesoporous carbon nanoparticles, wherein the ultra-small single mesoporous carbon nanoparticles are used as positive electrodes, zinc sheets are used as negative electrodes, and aqueous zinc salt electrolytes are used to assemble aqueous zinc ion batteries, which have excellent electrochemical properties, namely, higher discharge specific capacity, better cycle stability and smaller electrochemical impedance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the ultrasmall single mesoporous carbon nanoparticles prepared in Example 1 of the present invention.
[0025] Figure 2 This is a transmission electron microscopy image of the ultrasmall single mesoporous carbon nanoparticles prepared in Example 1 of the present invention.
[0026] Figure 3 This is a scanning electron microscope image of the ultrasmall single mesoporous carbon nanoparticles prepared in Example 2 of the present invention.
[0027] Figure 4 This is a scanning electron microscope image of the ultrasmall single mesoporous carbon nanoparticles prepared in Example 3 of the present invention.
[0028] Figure 5 This is a transmission electron microscopy image of the ultrasmall single mesoporous carbon nanoparticles prepared in Example 3 of the present invention.
[0029] Figure 6 This is a scanning electron microscope image of the ultrasmall single mesoporous carbon nanoparticles prepared in Example 4 of the present invention.
[0030] Figure 7This is a scanning electron microscope image of the ultrasmall single mesoporous carbon nanoparticles prepared in Example 5 of the present invention.
[0031] Figure 8 It is a bar chart of the specific capacity of the batteries assembled in Example 6 of the present invention and Comparative Examples 1-3.
[0032] Fig. 9 This is a cycle stability test diagram of the batteries assembled in Example 6 of the present invention and Comparative Examples 1-3.
[0033] Fig.10 The electrochemical impedance test diagram of the assembled batteries of Example 6 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0035] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs.
[0036] In the present invention, unless otherwise specified, the directions used, such as "up" and "down", usually refer to the directions shown in the drawings, or to the vertical, perpendicular or gravity directions; similarly, for ease of understanding and description, "left" and "right" usually refer to the left and right shown in the drawings; "inside" and "outside" refer to the inside and outside relative to the outline of each component itself, but the above-mentioned directions are not used to limit the present invention.
[0037] Embodiment 1: A method for preparing ultra-small single mesoporous carbon nanoparticles, comprising the following steps:
[0038] (1) Block copolymer micelles polystyrene-polyvinyl pyrrolidone-polyethylene glycol (PEO 113 -PVP 42 -PS 69 ) was used as a soft template, which was dissolved in an ethanol solution to obtain a block copolymer solution with a concentration of 15 mg / mL. The solution was then placed in an oven at 70°C for 3 hours and then cooled to room temperature to prepare a single micelle solution.
[0039] (2) 24.75 mL of deionized water, 16.25 mL of anhydrous ethanol and 9.0 mL of concentrated ammonia solution were mixed to obtain solution A, 4.50 mL of tetraethoxysilane was evenly dispersed in 45.5 mL of anhydrous ethanol to obtain solution B, the solution B was poured into the solution A, and the mixture was stirred at room temperature for 2 h; then 250 μL of dimethyldimethoxysilane was added, and the mixture was stirred for 2 h. After the reaction, SiO2 nanoparticles with a particle size of 200 nm were obtained by purification and drying;
[0040] (3) The SiO2 nanoparticles in step (2) are uniformly dispersed in anhydrous ethanol solution to form an SiO2 anhydrous ethanol solution with a concentration of 1 mg / mL, and then 2.0 mL of the single micelle solution in step (1) is added dropwise to the SiO2 anhydrous ethanol solution under magnetic stirring at a speed of 450 r / min. The reaction is stirred for 0.5 h, and then 25 μL of ammonia water is added to adjust the pH value to 7-9. After purification and drying, SiO2@single micelle superstructure nanoparticles are obtained;
[0041] (4) The superstructured nanoparticles in step (3) are uniformly dispersed in an anhydrous ethanol solution to form a superstructured nanoparticle alcohol solution with a concentration of 1-5 mg / mL, and then 6.0 mL of deionized water and 6.0 mg of bis(2-hydroxyethyl)aminotri(hydroxymethyl)methane buffer are added to 2.0 mL of the superstructured nanoparticle alcohol solution, and ultrasonic treatment is performed for 10 minutes to make it uniformly dispersed, and then 1.0 mg of dopamine hydrochloride is added, and the reaction is stirred at room temperature for 6 hours to obtain a polydopamine-encapsulated SiO2@single micelle complex;
[0042] (5) The composite in step (4) is centrifuged at a speed of 20,000 r / min, washed three times with deionized water, and then washed three times with a 95% ethanol solution, and dried at a temperature of 70°C for 15 h to obtain a pure sample, and then calcined in a nitrogen atmosphere at a heating rate of 3°C / min from room temperature to 525°C, and maintained for 5 h to obtain a SiO2@mesoporous carbon structure; finally, it is treated with a 2M sodium hydroxide solution at a treatment temperature of 30°C for 7 h, the mass ratio of the SiO2@mesoporous carbon structure to the sodium hydroxide solution is 1:100, and the silica template is removed to generate ultrasmall single mesoporous carbon nanoparticles.
[0043] The microstructure of the ultra-small single mesoporous carbon nanoparticles prepared in Example 1 was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 and Figure 2 As shown by Figure 1 and 2It can be seen that the size of the ultra-small single mesoporous carbon nanoparticles prepared in Example 1 is about 40-65 nm in diameter, the pore size and shape are relatively uniform, the diameter is about 15-20 nm, and the specific surface area of the material is as high as 1312 m 2 / g, and the shell thickness of the prepared ultrasmall single mesoporous carbon nanoparticles is about 12nm.
[0044] Example 2: The overall method is the same as that of Example 1, except that the block copolymer micelle is PEO 113 -PVP 47 -PS 106 .
[0045] The microstructure of the ultra-small single mesoporous carbon nanoparticles prepared in Example 2 was observed by scanning electron microscopy (SEM). Figure 3 As shown by Figure 3 It can be seen that the size of the ultra-small single mesoporous carbon nanoparticles prepared in Example 2 is about 40-65 nm in diameter, and the pore size is larger, about 20-25 nm in diameter, and the specific surface area of the material is 1050 m 2 / g, and the shell thickness of the prepared ultrasmall single mesoporous carbon nanoparticles is about 14 nm.
[0046] Example 3: The overall method is the same as that of Example 1, except that the block copolymer micelle is PEO 113 -PVP 63 -PS 140 .
[0047] The microstructure of the ultra-small single mesoporous carbon nanoparticles prepared in Example 3 was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 4 and Figure 5 As shown by Figure 4 and Figure 5 It can be seen that the diameter of the ultra-small single mesoporous carbon nanoparticles prepared in Example 3 is about 40-65 nm, and the pore size is significantly larger, about 26-30 nm, and the specific surface area of the material is 993 m 2 / g, and the shell thickness of the prepared ultrasmall single mesoporous carbon nanoparticles is about 14 nm.
[0048] Example 4: A method for preparing ultrasmall single mesoporous carbon nanoparticles, comprising the following steps:
[0049] (1) Block copolymer micelle polystyrene-polyacrylic acid-polyethylene glycol (PS-PAA-PEG) was used as a soft template and dissolved in an ethanol solution to obtain a block copolymer solution with a concentration of 0.2 mg / mL. The solution was then placed in an oven at 90°C for 4 hours and then cooled to room temperature to prepare a single micelle solution.
[0050] (2) 24.75 mL of deionized water, 16.25 mL of anhydrous ethanol and 9 mL of concentrated ammonia solution were mixed to obtain solution A, 4.5 mL of tetraethoxysilane was evenly dispersed in 45.5 mL of anhydrous ethanol to obtain solution B, the solution B was poured into the solution A, and the mixture was stirred at room temperature for 6 h; then 450 μL of dimethyldimethoxysilane was added, and the mixture was stirred for 0.5 h. After the reaction, SiO2 nanoparticles with a particle size of 100 nm were obtained by purification and drying;
[0051] (3) The SiO2 nanoparticles in step (2) are uniformly dispersed in anhydrous ethanol solution to form an SiO2 anhydrous ethanol solution with a concentration of 5 mg / mL, and then 2.0 mL of the single micelle solution in step (1) is added dropwise to the SiO2 anhydrous ethanol solution while stirring at a magnetic stirring speed of 300 r / min. The reaction is stirred for 3 h, and then 25 μL of ammonia water is added to adjust the pH value to 7-9, and then SiO2@single micelle superstructure nanoparticles are obtained after purification and drying;
[0052] (4) The superstructured nanoparticles in step (3) were uniformly dispersed in an anhydrous ethanol solution to form a superstructured nanoparticle alcohol solution with a concentration of 1 mg / mL. Then, 6.0 mL of deionized water and 6.0 mg of bis(2-hydroxyethyl)aminotri(hydroxymethyl)methane buffer were added to 2.0 mL of the superstructured nanoparticle alcohol solution, and ultrasonic treatment was performed for 5 minutes to make it uniformly dispersed. Then, 1.0 mg of dopamine hydrochloride was added and the reaction was stirred at room temperature for 2 hours to obtain a polydopamine-encapsulated SiO2@single micelle complex;
[0053] (5) The composite in step (4) was centrifuged at a speed of 8000 r / min, washed with deionized water for 3 times, and then washed with 95% ethanol solution for 3 times, and dried at a temperature of 50°C for 20 h to obtain a pure sample, and then calcined in a nitrogen atmosphere, with the temperature rising from room temperature to 350°C at a rate of 1°C / min, and maintained for 3 h to obtain a SiO2@mesoporous carbon structure; finally, it was treated with a 2M sodium hydroxide solution at a treatment temperature of 5°C for 10 h, and the mass ratio of the SiO2@mesoporous carbon structure to the sodium hydroxide solution was 1:50, and the silica template was removed to generate ultrasmall single mesoporous carbon nanoparticles.
[0054] The microstructure of the ultra-small single mesoporous carbon nanoparticles prepared in Example 4 was observed by scanning electron microscopy (SEM). Figure 6 As shown by Figure 6 It can be seen that the size diameter of the ultra-small single mesoporous carbon nanoparticles prepared in Example 4 is about 50-65 nm, the pore diameter is about 20-36 nm, and the specific surface area of the material is 1283 m 2 / g, and the shell thickness of the prepared ultrasmall single mesoporous carbon nanoparticles is about 15 nm.
[0055] Example 5: A method for preparing ultrasmall single mesoporous carbon nanoparticles, comprising the following steps:
[0056] (1) Block copolymer micelle polystyrene-polyacrylic acid (PS-PAA) was used as a soft template and dissolved in an ethanol solution to obtain a block copolymer solution with a concentration of 30 mg / mL. The solution was then placed in an oven at 110°C for 5 hours and then cooled to room temperature to prepare a single micelle solution.
[0057] (2) 24.75 mL of deionized water, 16.25 mL of anhydrous ethanol and 9 mL of concentrated ammonia solution were mixed to obtain solution A, 4.5 mL of tetraethoxysilane was evenly dispersed in 45.5 mL of anhydrous ethanol to obtain solution B, the solution B was poured into the solution A, and the mixture was stirred at room temperature for 6 h; then 250 μL of dimethyldimethoxysilane was added, and the mixture was stirred for 0.5 h. After the reaction, SiO2 nanoparticles with a particle size of 300 nm were obtained by purification and drying;
[0058] (3) The SiO2 nanoparticles in step (2) are uniformly dispersed in anhydrous ethanol solution to form an SiO2 anhydrous ethanol solution with a concentration of 10 mg / mL, and then 2.0 mL of the single micelle solution in step (1) is added dropwise to the SiO2 anhydrous ethanol solution while stirring at a magnetic stirring speed of 600 r / min. The reaction is stirred for 5 h, and then 30 μL of ammonia water is added to adjust the pH value to 7-9, and then SiO2@single micelle superstructure nanoparticles are obtained after purification and drying;
[0059] (4) The superstructured nanoparticles in step (3) were uniformly dispersed in anhydrous ethanol solution to form a superstructured nanoparticle alcohol solution with a concentration of 5 mg / mL. Then, 6.0 mL of deionized water and 6 mg of bis(2-hydroxyethyl)aminotri(hydroxymethyl)methane buffer were added to 2.0 mL of the superstructured nanoparticle alcohol solution, and ultrasonic treatment was performed for 15 minutes to make it uniformly dispersed. Then, 2 mg of dopamine hydrochloride was added and the reaction was stirred at room temperature for 10 hours to obtain a polydopamine-encapsulated SiO2@single micelle complex;
[0060] (5) The composite in step (4) is centrifuged at a speed of 40,000 r / min, washed three times with deionized water, and then washed three times with a 95% ethanol solution, and dried at a temperature of 80°C for 10 h to obtain a pure sample, and then calcined in a nitrogen atmosphere at a heating rate of 5°C / min from room temperature to 800°C, and maintained for 3 h to obtain a SiO2@mesoporous carbon structure; finally, it is treated with a 2M sodium hydroxide solution at a treatment temperature of 60°C for 4 h, and the mass ratio of the SiO2@mesoporous carbon structure to the sodium hydroxide solution is 1:120, and the silica template is removed to generate ultrasmall single mesoporous carbon nanoparticles.
[0061] The microstructure of the ultra-small single mesoporous carbon nanoparticles prepared in Example 5 was observed by scanning electron microscopy (SEM). Figure 7 As shown by Figure 7 It can be seen that the size diameter of the ultra-small single mesoporous carbon nanoparticles prepared in Example 5 is about 50-65 nm, the pore diameter is about 36-45 nm, and the specific surface area of the material is 1008 m 2 / g, and the shell thickness of the prepared ultrasmall single mesoporous carbon nanoparticles is about 13 nm.
[0062] Example 6: First, the ultra-small single mesoporous carbon nanoparticles prepared in Example 1, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. Then, n-methyl-2-pyrrolidone solvent was added and stirred for 5 hours to obtain a slurry. Secondly, the obtained slurry was coated on a stainless steel foil as a positive electrode. Finally, the above positive electrode, zinc sheet negative electrode, electrolyte (2 MZnSO4-7H2O) and glass microfiber separator were assembled into a button battery (CR2025 type) for further testing process.
[0063] Comparative Example 1: First, the raspberry-shaped mesoporous carbon spheres, conductive carbon black and polyvinylidene fluoride prepared by the prior art patent No. 202410010874.9, which discloses a raspberry-shaped mesoporous carbon sphere with a high specific surface area and a preparation method thereof, are mixed in a mass ratio of 8:1:1. Then, n-methyl-2-pyrrolidone solvent is added and stirred for 5 hours to obtain a slurry. Secondly, the obtained slurry is coated on a stainless steel foil as a positive electrode. Finally, the above-mentioned positive electrode, zinc sheet negative electrode, electrolyte (2 M ZnSO4-7H2O) and glass microfiber separator are assembled into a button battery (CR2025 type) for further testing process.
[0064] Comparative Example 2: First, existing non-porous hollow carbon spheres with a particle size of 45-55 nm, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. Then, n-methyl-2-pyrrolidone solvent was added and stirred for 5 hours to obtain a slurry. Secondly, the obtained slurry was coated on a stainless steel foil as a positive electrode. Finally, the above positive electrode, zinc sheet negative electrode, electrolyte (2 MZnSO4-7H2O) and glass microfiber separator were assembled into a button cell (CR2025 type) for further testing process.
[0065] Comparative Example 3: First, existing non-porous hollow carbon spheres with a particle size of 290-310 nm, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1. Then, n-methyl-2-pyrrolidone solvent was added and stirred for 5 hours to obtain a slurry. Secondly, the obtained slurry was coated on a stainless steel foil as a positive electrode. Finally, the above positive electrode, zinc sheet negative electrode, electrolyte (2 MZnSO4-7H2O) and glass microfiber separator were assembled into a button cell (CR2025 type) for further testing process.
[0066] Experiment: The aqueous zinc ion batteries assembled in Example 6, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were respectively subjected to charge and discharge tests. The results are as follows: Figure 8 As shown in Table 1, Figure 8 As can be seen from Table 1, the battery positive electrode prepared in Example 6 exhibits excellent electrochemical performance far higher than the performance of the batteries prepared in Comparative Example 1, Comparative Example 2 and Comparative Example 3. Therefore, the ultrasmall single mesoporous carbon nanoparticles prepared in the present invention have a higher discharge specific capacity.
[0067] Table 1 Discharge specific capacity test values
[0068]
[0069] The aqueous zinc ion batteries assembled in Example 6, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were subjected to cycle tests respectively. The results are as follows: Fig. 9 As shown by Fig. 9 It can be seen that the battery positive electrode prepared in Example 6 exhibits excellent cycle stability, which is much higher than the performance of the batteries prepared in Comparative Examples 1, 2 and 3. Therefore, the ultrasmall single mesoporous carbon nanoparticles prepared in the present invention have good cycle stability.
[0070] Electrochemical impedance tests were performed on the aqueous zinc ion batteries assembled in Example 6, Comparative Example 1, Comparative Example 2 and Comparative Example 3, and the results were as follows: Fig.10 As shown by Fig.10It can be seen that the positive electrode of the battery prepared in Example 6 exhibits a small impedance, which is much lower than the impedance of the batteries prepared in Comparative Examples 1, 2 and 3. Therefore, the ultrasmall single mesoporous carbon nanoparticles prepared in the present invention have a smaller electrochemical impedance.
[0071] The above experiments prove that the ultra-small single mesoporous carbon nanoparticles prepared by the present invention have a large specific surface area (1312 m 2 / g), with an ultra-small particle size of only 35-65nm, a large pore size and a unique pore structure (15-30 nm), which increases the active sites of chemical reactions, can provide better material transmission channels, and has a fast mass transfer power, so that the electrolyte can diffuse rapidly in the particles through the radial pores, and the electrochemical performance of the material is significantly improved. Therefore, the aqueous zinc ion battery assembled with it as the positive electrode, the zinc sheet as the negative electrode, and the aqueous zinc salt electrolyte has excellent electrochemical performance compared to the positive electrode materials disclosed in Comparative Examples 1-3, that is, it has a higher discharge specific capacity, better cycle stability and smaller electrochemical impedance.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0073] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing ultra-small single mesoporous carbon nanoparticles, characterized in that: It includes the following steps: (1) Preparing a single micelle solution: using a block copolymer as a soft template, dissolving it in an ethanol solution to obtain a block copolymer solution with a concentration of 0.2-30 mg / mL, and then using a thermodynamic control method to prepare a single micelle solution; (2) Preparation of SiO2 nanoparticles: deionized water, anhydrous ethanol and concentrated ammonia solution are mixed in a mass ratio of 10-20:1-24:5-10 to obtain solution A, tetraethoxysilane and anhydrous ethanol are mixed in a mass ratio of 10-50:1-5 to obtain solution B, the solution B is poured into the solution A, and stirred at room temperature for reaction for 2-10 hours; then dimethyldimethoxysilane is added, and stirred for reaction for 2-10 hours. After the reaction, SiO2 nanoparticles of 100-300 nm are obtained by purification and drying; the mass ratio of the solution B, the solution A and the dimethyldimethoxysilane is 16-54:11-55:0.4-2.0; (3) Preparation of SiO2@single micelle superstructure nanoparticles: The SiO2 nanoparticles in step (2) are uniformly dispersed in an anhydrous ethanol solution to form an SiO2 anhydrous ethanol solution with a concentration of 1-10 mg / mL. Then, the single micelle solution in step (1) is added dropwise to the SiO2 anhydrous ethanol solution under stirring. Ammonia water is then added to adjust the pH value to 7-9. After purification and drying, SiO2@single micelle superstructure nanoparticles are obtained. (4) Preparation of SiO2@single micelle complex: The superstructured nanoparticles in step (3) are uniformly dispersed in anhydrous ethanol solution to form a superstructured nanoparticle alcohol solution with a concentration of 1-5 mg / mL. Deionized water and bis(2-hydroxyethyl)aminotri(hydroxymethyl)methane buffer are then added to the superstructured nanoparticle alcohol solution, and ultrasonic treatment is performed for 5-15 minutes to make it uniformly dispersed. Dopamine hydrochloride is then added and the reaction is stirred at room temperature for 2-10 hours to obtain a polydopamine-encapsulated SiO2@single micelle complex. (5) Preparation of ultrasmall single mesoporous carbon nanoparticles: The composite in step (4) is centrifuged, washed, and dried in sequence to obtain a pure sample, and then calcined in a nitrogen atmosphere at a heating rate of 1-5°C / min from room temperature to 350-800°C and maintained for 3-10h to obtain a SiO2@mesoporous carbon structure; finally, it is treated with a sodium hydroxide solution at a treatment temperature of 5-60°C for a treatment time of 4-10h to remove the silica template to generate ultrasmall single mesoporous carbon nanoparticles.
2. The method for preparing ultrasmall single mesoporous carbon nanoparticles according to claim 1, characterized in that: The block copolymer in step (1) is any one of polystyrene-polyvinyl pyrrolidone-polyethylene glycol, polystyrene-polyacrylic acid-polyethylene glycol, polymethyl methacrylate-polyvinyl pyrrolidone-polyethylene glycol, polystyrene-polyvinyl pyrrolidone, and polystyrene-polyacrylic acid.
3. The method for preparing ultrasmall single mesoporous carbon nanoparticles according to claim 1, characterized in that: In the step (1), the temperature of the thermodynamic control method is 70-110° C. and the time is controlled to be 3-5 hours.
4. The method for preparing ultrasmall single mesoporous carbon nanoparticles according to claim 1, characterized in that: The stirring in steps (2), (3) and (4) is performed using a magnetic stirrer at a speed of 300-600 r / min for a time of 0.5-5 h.
5. The method for preparing ultrasmall single mesoporous carbon nanoparticles according to claim 1, characterized in that: In the step (3), the volume ratio between the SiO2 anhydrous ethanol solution and the single micelle solution is 1:0.5-5.
6. The method for preparing ultrasmall single mesoporous carbon nanoparticles according to claim 1, characterized in that: In the step (4), the mass ratio of the superstructured nanoparticle alcohol solution, the deionized water, the buffer and the dopamine hydrochloride is 1:1-5:0.002-1:0.002-1.
7. The method for preparing ultrasmall single mesoporous carbon nanoparticles according to claim 1, characterized in that: In the step (5), the centrifugal speed is 8000-40000 r / min, the washing conditions are washing with deionized water and 95% ethanol solution for 2-6 times respectively; the drying temperature is 50-80°C, and the drying time is 10-20h; the concentration of the sodium hydroxide solution is 2M, and the mass ratio of the SiO2@mesoporous carbon structure to the sodium hydroxide solution is 1:50-120.
8. The ultra-small single mesoporous carbon nanoparticles prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The ultra-small single mesoporous carbon nanoparticles are hollow in structure, with open pores on the shell surface of the ultra-small single mesoporous carbon nanoparticles. The particle size of the ultra-small single mesoporous carbon nanoparticles is 35-65nm; the specific surface area is 993-1312m 2 / g.
9. The use of the ultra-small single mesoporous carbon nanoparticles in a battery as claimed in claim 8, characterized in that: The ultra-small single mesoporous carbon nanoparticles are used as positive electrodes, zinc sheets are used as negative electrodes, and aqueous zinc salt electrolytes are used to assemble aqueous zinc ion batteries.
Citation Information
Patent Citations
Aqueous zinc ion battery electrolyte and application thereof
CN111900497A
Micellar-silicon dioxide asymmetric hybrid material and preparation method thereof
CN117343467A
Raspberry-shaped mesoporous carbon sphere with high specific surface area and preparation method of raspberry-shaped mesoporous carbon sphere
CN117534058A
Preparation method of nano silicon dioxide particles
CN119219002A